O erro produzido pelo aluno no contexto pedagógico: uma luz ou uma pedra no meio do caminho? - Salsa, Ivone da Silva (2010)
Student’s mistakes as viewed in a didactic and pedagogical perspective are a phenomenon inevitably observed in any context in which formal teaching-andlearning processes are taking place. Researchers have shown that such mistakes are viewed most of the times as undesirable and often as a consequence of lack of attention or poor commitment on the part of the student and rarely considered didactically useful. The object of our reflections in this work is exactly those mistakes, which are born in the entrails of the teaching-and-learning processes. It is our understanding that a mistake constitutes a tool which mediates knowledge and may therefore become a strong ally of the instructor’s actions in her/his teaching tasks and thus should be taken into the teacher’s best consideration. Understanding a mistake as so, we postulate that the teacher must face it as a possibility to be exploited rather than as a negative occurrence. Such an attitude on the part of the teacher would undoubtedly render profitable didactic situations. To deepen the understanding of our aim, we took a case study on the perception of senior college students in the program of Mathematics at UFRN in the year 2009, 2nd term. The reason of this choice is the fact that Mathematics is the field presenting traditionally the poorest records in terms of school grades. In this work we put forth data associated to ENEM1 , to the UFRN Vestibular2 and the undergraduate courses on Mathematics. The theoretical matrixes supporting our reflections in this thesis follow the ideas proposed by Castorina (1988); Davis e Espósito (1990); Aquino (1997); Luckesi (2006); Cury (1994; 2008); Pinto (2000); Torre (2007). To carry out the study, we applied a semi-structured questionnaire containing 14 questions, out of which 10 were open questions. The questions were methodologically based on the Thematic Analysis – One of the techniques for Content Analysis schemed by Bardin (1977) – and it was also used the computer program Modalisa 6.0 (A software designed by faculties the University of Paris VIII). The results indicate that most of the teachers training instructors in their pedagogical practice view the mistakes made by their students only as a guide for grading and, in this procedure, the student is frequently labeled as guilty. Conclusive analyses, therefore, signal to the necessity of orienting the teachers training instructors in the sense of building a new theoretical contemplation of the students’ mistakes and their pedagogical potentialities and so making those professionals perceive the importance of such mistakes, since they reveal gaps in the process of learning and provide valuable avenues for the teaching procedures.